Study of surfactants influence on the noopept releasing from the nasal dosage form - B. S. Burlaka; I. F. Bielenichev; V. V. Hladyshev (Zaporozhye State Medical University, 2020)
The nasal route of drug administration, as is well known, is characterized by some advantages: absorption rate and rapid onset of therapeutic effect, availability of drug delivery without hepatic first-pass elimination, it is suitable and easily accessible. Earlier a medication for nasal administration with noopept - a low toxic substance with peptide nature without any side effects and high activity has been developed. After advance investigations, a solution of sodium carboxymethylcellulose providing the highest rate of noopept releasing was chosen as a delivery base. The aim of work the study of surfactants' influence on the noopept releasing from the nasal dosage form. Materials and methods. For the investigation, the compositions containing twin-80 from 0 % to 3 % were prepared. Surfactant was added to the nasal dosage form containing noonpept 1 %, glycerol, and bishofit poltavsky equally by 5 % and solution of sodium carboxymethylcellulose. Noopept releasing was studied using the method of equilibrium dialysis by Kruvchinsky through the semipermeable membrane - cellophane film "Kuprofan" after 30 minutes. Noopept concentration was determined by the UV-spectrophotometry at 258 nm. Results. Results of investigation have verified that the addition of twin-80 to nasal dosage form with noopept provides with a better level of releasing of the active substance. At the same time, increasing of concentration more than 1 % hasn't a significant influence on the noopept releasing. Conclusions. It was determined that the content of twin-80 has a significant influence on a noopept releasing from the nasal dosage forms. The concentration of twin-80 1 % provides optimal releasing.